Feature writing and reporting : journalism in the digital age - Cox, Jennifer B. (Los Angeles, CA : SAGE Publications, Inc., 2021)
Feature Writing and Reporting: Journalism in the Digital Age teaches students the fundamental skills of great feature reporting and writing, while emphasizing the skills and tools needed to be successful in the digital news era. Packed with numerous examples culled from the best samples of feature writing today, this text provides ample opportunity to practice writing while building a portfolio of work to prepare students for their future careers. A special emphasis on new multimedia and online reporting primes readers for success in a rapidly changing media landscape.
Description based on XML content.
Includes index.
Keywords: Online journalism -- Textbooks; Reporters and reporting -- Textbooks; Digital media -- Editing -- Textbooks